Outcomes of Conventional Phototherapy versus Fiberoptic Phototherapy in the Management of Neonatal Jaundice - Rizwan Mahmood, Imran Yasin, Husnul Hayat, Khurram Nawaz, Muhammad Usman Rafique, Sanwal Sardar Nawaz, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Neonatal jaundice is a common clinical condition affecting a large proportion of newborns worldwide. Objective: To evaluate and compare the outcomes of conventional phototherapy versus fiberoptic phototherapy in the management of neonatal jaundice. Methodology: This comparative cross-sectional study was conducted at Department of Pediatrics, Sahara Medical College Narowal from 1st March 2023 to 31st August 2023 among 260 neonates diagnosed with neonatal jaundice. Participants were randomly assigned to receive either conventional phototherapy using blue fluorescent lamps (Group A, n = 130) or fiberoptic phototherapy via bili-blanket systems (Group B, n = 130). Serum total bilirubin (STB) levels were measured before treatment and every 12 hours until normalization. Results: The mean baseline bilirubin levels were comparable between the two groups (17.6±2.4 mg/dL vs. 17.4±2.6 mg/dL; p=0.59). After 24 hours, the mean bilirubin reduction was significantly higher in the conventional group (6.1±1.8 mg/dL) compared to the fiberoptic group (4.9±1.7 mg/dL; p<0.001). The average duration of therapy was shorter with conventional phototherapy (28.5±6.3 hours) than with fiberoptic therapy (36.8±7.5 hours; p < 0.001). However, fiberoptic phototherapy showed fewer side effects, with lower incidences of hyperthermia (4.6% vs. 13.1%; p = 0.02) and dehydration (3.8% vs. 11.5%; p = 0.03). No cases required exchange transfusion, and rebound hyperbilirubinemia rates were similar (p = 0.62). Conclusion: Both conventional and fiberoptic phototherapy are effective in reducing serum bilirubin in neonates with jaundice. Conventional phototherapy provides faster bilirubin clearance and shorter treatment duration, while fiberoptic phototherapy offers improved safety, comfort, and bonding opportunities. Keywords: Neonatal jaundice, Phototherapy, Fiberoptic bili-blanket, Hyperbilirubinemia